Javanese Phonology Variaton Of Cirebon Dialect At Dawuan Village - Utami Rosalina; Juwintan Juwintan; Yosi Ayu Pratiwi (Journal Of Social Science (JoSS), 2022)
This research focused on language variations that used by the people of Dawuan Village, Sub-District of Cirebon Regency. This research aimed to described kinds of phonemes variations of Cirebon dialect by the people of Dawuan Village. This research used descriptive qualitative method. The writer used data collections method through direct observation and interview by the people of Dawuan Village as much as 18 people from 12 to 65 years old both women and men. The result showed that there are 111 phonological variations in the form of variations vowels phonemes (56), variations vowels – consonant phonemes (2), and variations of consonant phonemes (53) at Dawuan Village. This result obtained by using 207 words Swadesh List and 169 additional words submitted as questions to the local people.